Anthropomorphism in Upin dan Ipin: A Study of Children’s Literature - Aris, Qori Islami; Syam, Essy (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
This study discusses the use of anthropomorphism in two episodes of Upin and Ipin entitled Aku Sebatang Pensel and Aku Sebuah Jam. Through observation and note-taking techniques, data were obtained to analyze how the two episodes humanize pencils and clocks. The results of the analysis show the presence of anthropomorphic elements in both episodes, including human characters, emotions, and human behavior given to pencils and clocks. The pencils in the episode Aku Sebatang Pensel behave like humans with the ability to speak, interact, and show emotions such as worry, anger, pride, sadness, and joy. Meanwhile, the clock characters in the episode Aku Sebuah Jam also show human behavior with the ability to speak, share experiences, show concern, and dance. Sad emotions are also displayed by the clock characters. The characteristics of pencil and clock characters include helpful, encouraging, caring, argumentative, passionate, optimistic, cheerful, curious, obedient, and expressive. This study uncovers the use of anthropomorphism in Upin and Ipin animations, shedding light on its contribution to children's imagination, understanding of complex issues, and story appeal. Through this technique, young audiences can connect with the characters and develop empathy. The findings are relevant for the development of children's films and learning media, as an effective strategy to convey moral values. The study also encourages animation and creative producers to produce creative and diverse content, in line with the demands of complex audiences.